ANTISIPASI PENDUDUK DALAM MENGHADAPI BANJIR KALI GARANG KOTA SEMARANG (Forum Ilmu Sosial, 2008)
The area of floods tends to be increased. This is happened because of natural phenomenon and humanmisbehavior. Floods of Kaligarang were happened because of clogged up-drainage, lack of people’sawareness on sanitation, lack of expense for activity of flood anticipatory. More over, the governmentwas not responsive enough to anticipate floods and the altitudes of some area are below or equal thesea level surface. The amount of unsuccessful flood anticipation in Kaligarang’s downstream was 57location samples (82,61%), while the amount of successful flood anticipation was only 12 locationsamples (17,39%). Floods anticipatory can be conducted technically and non-technically. Technically,anticipation involves heightening houses/building, making dike, normalizing drainage, dredging, makingdrainage, making by pass and flood ways, making pumping station, making ‘sudetan’, and making barrage.Non-technically anticipation involves management of floods plan, benefiting of river surrounding areas,arranging farm plantation, and community socialization.Keywords: Community anticipation, Kaligarang flood